Facile and scalable synthesis of reduced-graphene oxide using different green reducing agents and its characterizations - Verma S.; Das T.; Pandey V.K.; Verma B. (My University, 2025)
In the present paper, Graphene oxide (GO) has been synthesized by the exfoliation of graphite sheets using improved Hummer's method, and further reduction occurs by using different green reducing agents like betel leaves, lemon grass, red-rose leaves, and green tea leaves extract to form reduced-graphene oxide (rGO). The obtained GO and different rGO were further characterized by using XRD, Raman spectroscopy, FTIR, HR-SEM, EDX, UV visible absorption and TGA. The different parameters like crystallite size, d-spacing, the number of graphene layers, lattice strain, and defect density were also determined by using XRD and Raman technique. The particle size distribution indicates that rGO3 (Red-rose leaves extract) has lower in size compared to all other samples. Linear I–V and Nyquist study shown that rGO3 has generate high current and low inherent resistance, respectively. So, the material rGO3 can be used as a base material in the field of energy storage application. © 2022 Elsevier B.V.